Hell and back [compact disc, unabridged] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2022)
There is something out there in Montana's yellowed skies that the Northern Cheyenne refer to as the Stealer of Souls. Now Sheriff Longmire must battle with his most dangerous advisory ever, himself.